LIVE BED SCOUR AT A SIDE-WEIR INTERSECTION LOCATED ON AN ALLUVIAL CHANNEL - Onen, F.; Agaccioglu, H. (WILEY-BLACKWELL, 2013)
This study aims to obtain both the depth of clear water and live bed scour around side-weirs located on an alluvial channel for sharp-crested side-weirs under subcritical flow conditions. At the downstream end of the side-weir, a longitudinal bar in the middle of the channel and a scour hole close to the outer bank are formed because of changes in shear stress field and velocities. Dimensionless depth of scour increases with an increase of the dimensionless parameters of flow depth, side-weir length and sediment size. The dimensionless depth of scour increases almost linearly with the dimensionless parameter of flow velocity for clear water scour, and it decreases for live bed conditions at the straight channel due to the decreasing deviation angle and kinetic energy toward the side-weirs and bed material coming from upstream of the main channel. Because of the effect of the helicoidal flow created by bends, the dimensionless depth of scour fluctuated with the dimensionless parameter of flow velocity at the maximum value of clear water scour for movable bed conditions at a bend. At the 30 degrees section of a bend, the equilibrium depth of scour is achieved as maximum values due to the deviation on the path of maximum velocity towards the outer bank. Copyright (c) 2013 John Wiley & Sons, Ltd.
Keywords: side-weir; clear-water scour; live bed scour: curved flow; curved channel; DISCHARGE COEFFICIENT; BRIDGE PIERS; CURVED CHANNELS; FLOW; Agriculture; Water Resources